Implementasi Kombinasi Metode ROC dan MAUT Dalam Menentukan Aplikasi Chatting Terbaik - Hetty Rohayani; M. Reinaldi; Bister Purba (Journal of Computing and Informatics Research, 2024)
The rapid development of technology makes it easier for humans to communicate with each other more easily by using the best chatting applications. The purpose of this research is to help users who have just used a smartphone to choose the chatting application that suits their needs. The method used in this study is a Decision Support System with Rank Order Centroid (ROC) as the weight value and Multi Attribute Utility Theory (MAUT) as a solution. The alternatives used are Whatsapp, Messager, Discord, Telegram, Line, WeChatting and the criteria used are Security, Storage Media, Network Usage, application features, Display / Interface. The results obtained indicate that the Whatsapp alternative is the first recommendation as the best chatting application with a final value of 0.929456. The Telegram alternative became the second recommendation with a final value of 0.847485 and Line became the third recommendation with a final value of 0,624656.